Quality of Chicken Sausage during Storage with Addition of Andaliman Fruit Powder - Julianti, Elisa; Lubis, Zulkifli; Hilman, Adrian (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The study aimed to evaluate the impact of Andaliman Fruit Powder (AFP) concentrations ranging from 0.5 to 1.5% on the quality of chicken sausages over a 4-week storage period. The result showed that a higher concentration of AFP had a significant (p<0.05) increase in total phenolics and total flavonoids, while the total microbes and free fatty acid content decreased. There were no significant differences (p>0.05) observed in the protein content, pH, texture, and panelists' acceptance of color, aroma, and taste in comparison with the control. The incorporation of 1.5% AFP can be applied to maintain the quality of chicken sausage during storage at 10°C.